ENT300 La Belleza Enterprise / Alphonsus Obbermann Anchang... [et al.] - Anchang, Alphonsus Obbermann; Awang Halmi, Dayang Hamizah; Sambang, Feilycia; Lawrence, Nur Sorfina; Hasni, Nurul Aiman; Aduka, Siti Zunika (2015)
La Belleza Enterprise is a clothing boutique that offers updated fashion trend at a cheap nad affordable price along with high quality material. Our boutique is located at Batu Kawa, near to Emart Hypermarket. We offer clothes for unisex, ageing from 15 to 40 years old. We offer variety category of clothes from, women blouses, skirts, shawls, pants, men shirts and others. While there are many competitors to our boutique, La Belleza will excel as we ensure our price is at affordable price range along with high quality products that we offer. On top of that, we ensure that our product will be keep up to date with the current fashion trend in line with the fashion Industry. We also provide plus size to our customers in order to ensure there is no discrimination to our customer.